Strategy to discover full-length amyloid-beta peptide ligands using high-efficiency microarray technology - Galati, Clelia; Spinella, Natalia; Renna, Lucio; Milardi, Danilo; Attanasio, Francesco; Sciacca, Michele Francesco Maria; Bongiorno, Corrado (Beilstein Journal of Nanotechnology, 2017)
Although the formation of β-amyloid (Aβ) fibrils in neuronal tissues is a hallmark of Alzheimer disease (AD), small-sized Aβ oligomers rather than mature fibrils have been identified as the most neurotoxic species. Therefore, the design of new inhibitors, able to prevent the aggregation of Aβ, is believed to be a promising therapeutic approach to AD. Unfortunately, the short-lived intermediate structures that occur in a solution along the Aβ aggregation pathway escape conventional experimental investigations and there is urgent need of new tools aimed at the discovery of agents targeting monomeric Aβ and blocking the early steps of amyloid aggregation. Here, we show the combination of high-efficiency slides (HESs) with peptide microarrays as a promising tool for identifying small peptides that bind Aβ monomers. To this aim, HESs with two immobilized reference peptides, (i.e., KLVFF and Semax) with opposite behavior, were investigated for binding to fluorescently labeled Aβ peptide. Transmission electron microscopy was used to demonstrate Aβ fibrillar aggregates missing. The use of HESs was critical to ensure convenient output of the fluorescent microarrays. The resulting sensitivity, as well as the low sample consumption and the high potential for miniaturization, suggests that the proposed combination of peptide microarrays and highly efficient slides would be a very effective technology for molecule profiling in AD drug discovery.
Keywords: Alzheimer's disease; florescence; high sensitivity; peptide; silicon oxide; TEM

(untitled) - Hardy, J. (Neurobiol. Aging, 2002)

(untitled) - Kang, J.; Lemaire, H.-G.; Unterbeck, A.; Salbaum, J. M.; Masters, C. L.; Grzeschik, K.-H.; Multhaup, G.; Beyreuther, K.; Müller-Hill, B. (Nature, 1987)

(untitled) - Haass, C.; Selkoe, D. J. (Nat. Rev. Mol. Cell Biol., 2007)

(untitled) - Giuffrida, M. L.; Caraci, F.; Pignataro, B.; Cataldo, S.; De Bona, P.; Bruno, V.; Molinaro, G.; Pappalardo, G.; Messina, A.; Palmigiano, A.; Garozzo, D.; Nicoletti, F.; et al. (J. Neurosci., 2009)

(untitled) - Wennmalm, S.; Chmyrov, V.; Widengren, J.; Tjernberg, L. (Anal. Chem., 2015)

(untitled) - Frid, P.; Anisimov, S. V.; Popovic, N. (Brain Res. Rev., 2007)

(untitled) - Solomon, B. (Curr. Opin. Invest. Drugs (BioMed Cent.), 2007)

(untitled) - Yang, D.-S.; Yip, C. M.; Huang, T. H. J.; Chakrabartty, A.; Fraser, P. E. (J. Biol. Chem., 1999)

(untitled) - Begum, A. N.; Jones, M. R.; Lim, G. P.; Morihara, T.; Kim, P.; Heath, D. D.; Rock, C. L.; Pruitt, M. A.; Yang, F.; Hudspeth, B.; Hu, S.; Faull, K. F.; et al. (J. Pharmacol. Exp. Ther., 2008)

(untitled) - Attanasio, F.; Convertino, M.; Magno, A.; Caflisch, A.; Corazza, A.; Haridas, H.; Esposito, G.; Cataldo, S.; Pignataro, B.; Milardi, D.; Rizzarelli, E. (ChemBioChem, 2013)

(untitled) - De Bona, P.; Giuffrida, M. L.; Caraci, F.; Copani, A.; Pignataro, B.; Attanasio, F.; Cataldo, S.; Pappalardo, G.; Rizzarelli, E. (J. Pept. Sci., 2009)

(untitled) - Soto, C.; Sigurdsson, E. M.; Morelli, L.; Kumar, R. A.; Castaño, E. M.; Frangione, B. (Nat. Med., 1998)

(untitled) - Soto, P.; Griffin, M. A.; Shea, J.-E. (Biophys. J., 2007)

(untitled) - Bieschke, J.; Russ, J.; Friedrich, R. P.; Ehrnhoefer, D. E.; Wobst, H.; Neugebauer, K.; Wanker, E. E. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Brener, O.; Dunkelmann, T.; Gremer, L.; van Groen, T.; Mirecka, E. A.; Kadish, I.; Willuweit, A.; Kutzsche, J.; Jürgens, D.; Rudolph, S.; Tusche, M.; Bongen, P.; et al. (Sci. Rep., 2015)

(untitled) - Rzepecki, P.; Nagel-Steger, L.; Feuerstein, S.; Linne, U.; Molt, O.; Zadmard, R.; Aschermann, K.; Wehner, M.; Schrader, T.; Riesner, D. (J. Biol. Chem., 2004)

(untitled) - Sciacca, M. F. M.; Romanucci, V.; Zarrelli, A.; Monaco, I.; Lolicato, F.; Spinella, N.; Galati, C.; Grasso, G.; D’Urso, L.; Romeo, M.; Diomede, L.; Salmona, M.; et al. (ACS Chem. Neurosci., 2017)

(untitled) - Grasso, G.; Santoro, A. M.; Lanza, V.; Sbardella, D.; Tundo, G. R.; Ciaccio, C.; Marini, S.; Coletta, M.; Milardi, D. (Coord. Chem. Rev., 2017)

(untitled) - Pannuzzo, M.; Milardi, D.; Raudino, A.; Karttunen, M.; La Rosa, C. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Pannuzzo, M.; Raudino, A.; Milardi, D.; La Rosa, C.; Karttunen, M. (Sci. Rep., 2013)

(untitled) - Chen, J.; Armstrong, A. H.; Koehler, A. N.; Hecht, M. H. (J. Am. Chem. Soc., 2010)

(untitled) - Harper, J. D.; Lansbury, P. T. (Annu. Rev. Biochem., 1997)

(untitled) - O’Nuallain, B.; Shivaprasad, S.; Kheterpal, I.; Wetzel, R. (Biochemistry, 2005)

(untitled) - Volle, J.-N.; Chambon, G.; Sayah, A.; Reymond, C.; Fasel, N.; Gijs, M. A. M. (Biosens. Bioelectron., 2003)

(untitled) - Bras, M.; Dugas, V.; Bessueille, F.; Cloarec, J. P.; Martin, J. R.; Cabrera, M.; Chauvet, J. P.; Souteyrand, E.; Garrigues, M. (Biosens. Bioelectron., 2004)

(untitled) - Arrabito, G.; Galati, C.; Castellano, S.; Pignataro, B. (Lab Chip, 2013)

(untitled) - Cretich, M.; di Carlo, G.; Longhi, R.; Gotti, C.; Spinella, N.; Coffa, S.; Galati, C.; Renna, L.; Chiari, M. (Anal. Chem., 2009)

(untitled) - Cretich, M.; Galati, C.; Renna, L.; Condorelli, G. G.; Gagni, P.; Chiari, M. (Sens. Actuators, B, 2014)

(untitled) - Chalifour, R. J.; McLaughlin, R. W.; Lavoie, L.; Morissette, C.; Tremblay, N.; Boulé, M.; Sarazin, P.; Stéa, D.; Lacombe, D.; Tremblay, P.; Gervais, F. (J. Biol. Chem., 2003)

(untitled) - Tjernberg, L. O.; Näslund, J.; Lindqvist, F.; Johansson, J.; Karlström, A. R.; Thyberg, J.; Terenius, L.; Nordstedt, C. (J. Biol. Chem., 1996)

(untitled) - Rzepecki, P.; Steger, L. N.; Feuerstein, S.; Linne, U.; Molt, O.; Zadmard, R.; Aschermann, K.; Wehner, M.; Schrader, T.; Riesner, D. (J. Neurochem., 2006)

(untitled) - Ashmarin, I. P.; Nezavibatko, V. N.; Myasoedov, N. F.; Kamenskii, A. A.; Grivennikov, I. A.; Ponomareva-Stepnaya, M. A.; Andreeva, L. A.; Kaplan, A. Y.; Kosheleva, V. B.; Ryasina, T. V. (Zh. Vyssh. Nervn. Deyat. im. I. P. Pavlova, 1997)

(untitled) - Bashkatova, V. G.; Koshelev, V. B.; Fadyukova, O. E.; Alexeev, A. A.; Vanin, A. F.; Rayevsky, K. S.; Ashmarin, I. P.; Armstrong, D. M. (Brain Res., 2001)

(untitled) - Potaman, V. N.; Antonova, L. V.; Dubynin, V. A.; Zaitzev, D. A.; Kamensky, A. A.; Myasoedov, N. F.; Nezavibatko, V. N. (Neurosci. Lett., 1991)

(untitled) - Storozhevykh, T. P.; Tukhbatova, G. R.; Senilova, Ya. E.; Pinelis, V. G.; Andreeva, L. A.; Myasoyedov, N. F. (Bull. Exp. Biol. Med., 2007)

(untitled) - Tabbì, G.; Magrì, A.; Giuffrida, A.; Lanza, V.; Pappalardo, G.; Naletova, I.; Nicoletti, V. G.; Attanasio, F.; Rizzarelli, E. (J. Inorg. Biochem., 2015)

(untitled) - Seilheimer, B.; Bohrmann, B.; Bondolfi, L.; Müller, F.; Stüber, D.; Döbeli, H. (J. Struct. Biol., 1997)

(untitled) - Hansson, O.; Zetterberg, H.; Peder, B. P.; Andreasson, U.; Londos, E.; Minthon, L.; Blennow, K. (Dementia Geriatr. Cognit. Disord., 2007)

(untitled) - Goldsbury, C. S.; Wirtz, S.; Müller, S. A.; Sunderji, S.; Wicki, P.; Aebi, U.; Frey, P. (J. Struct. Biol., 2000)

(untitled) - Morales-Narváez, E.; Montón, H.; Fomicheva, A.; Merkoçi, A. (Anal. Chem., 2012)

U.S. Patent - Renna, L.; Galati, C.; Spinella, N. M. R.; Coffa, S. (Optically Accessible Microfluidic Diagnostic Device, 2011)

(untitled) - Sinopoli, A.; Magrì, A.; Milardi, D.; Pappalardo, M.; Pucci, P.; Flagiello, A.; Titman, J. J.; Nicoletti, V. G.; Caruso, G.; Pappalardo, G.; Grasso, G. (Metallomics, 2014)

(untitled) - Renna, L.; Galati, C.; Spinella, N.; Mazzillo, M.; Abbisso, S.; Fallica, P. G. (Sens. Actuators, B, 2015)